Upper and lower Lebesgue classes of multivalued functions of two variables - Karlova, O. O.; Mykhailyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We introduce a functional Lebesgue classification of multivalued mappings and obtain results on upper and lower Lebesgue classifications of multivalued mappings F : X × Y Z for wide classes of spaces X, Y and Z.